Histone lactylation drives liver cancer metastasis by facilitating NSF1-mediated ferroptosis resistance after microwave ablation - Jiayan Huang; Huijing Xie; Ju Li; Xiaotong Huang; Yunshi Cai; Rui Yang; Dongmei Yang; Wuyongga Bao; Yongjie Zhou; Tao Li; Qiang Lu (Redox Biology)
Insufficient microwave ablation (IMWA) is linked to aggressive hepatocellular carcinoma (HCC) progression. An increase in lactate levels after sublethal heat stress (HS) has been confirmed in HCC. However, the role of lactate-related histone lactylation in the progression of HCC caused by sublethal HS remains unclear. Here, we found that the metastatic potential of HCC increased in a lactate-dependent manner after IMWA. Moreover, sublethal HS triggered an increase in H3K18la modification, as validated in a cell-derived xenograft mouse model and human HCC samples. By performing an integrated analysis of proteomic and transcriptomic profiles, we revealed that HCC cells exhibited increased intracellular iron ion homeostasis and developed resistance to platinum-based drugs after exposure to sublethal HS. We subsequently integrated proteomic and transcriptomic data with H3K18la-specific chromatin immunoprecipitation (ChIP) sequencing to identify candidate genes involved in sublethal heat treatment-induced HCC cell metastasis. Mechanically, an increase in H3K18la modification enhanced the transcriptional activity of NFS1 cysteine desulfurase (NFS1), a key player in iron‒sulfur cluster biosynthesis, thereby reducing the susceptibility of HCC to ferroptosis after IMWA. Knocking down NFS1 diminished the metastatic potential of sublethally heat-treated HCC cells. Additionally, NFS1 deficiency exhibited a synergistic effect with oxaliplatin, leading to the significant inhibition of the metastatic capability of HCC cells both in vitro and in vivo, regardless of sublethal HS treatment. In conclusion, our study revealed the oncogenic role of histone lactylation in HCC after IMVA. We also bridged histone lactylation with ferroptosis, providing novel therapeutic targets for HCC following microwave ablation, particularly when combined with oxaliplatin-based chemotherapy.